Hypothyroidism in pregnancy: An alarming concern in a rural community of Eastern India - Sarika Palepu; Arvind Kumar Singh; Goutam Kumar Saharia; Suravi Patra; Sweta Singh; Manish Taywade; Vikas Bhatia (Wolters Kluwer Medknow Publications, 2023)
Introduction: Hypothyroidism exerts a multitude of effects on pregnant women and newborns. This study aimed to estimate the prevalence of hypothyroidism and its associated factors among pregnant women. Material and Methods: This cross-sectional study was done at a community health center in Tangi, Eastern India. A total of 436 pregnant women ≤24 weeks gestation attending the ante-natal clinic were recruited by consecutive sampling after obtaining written informed consent. Those who were a known case of any psychiatric disorder and were not able to comprehend interview questions were excluded. Estimation of serum thyroid stimulating hormone levels was done at the central laboratory of the All India Institute of Medical Sciences, Bhubaneswar. Analysis was done using STATA 17.0 and presented as means or proportions. The association of hypothyroidism with various sociodemographic factors was analyzed with bivariate logistic regression. Results: Mean age of the study participants was 23.9 years (SD: 3.65). About 31.4% of participants were found to have hypothyroidism. On bivariate logistic regression, the presence of hypothyroidism was not associated with any variable. Conclusions: Hypothyroidism is widely prevalent in pregnant females in rural India. Screening of high-risk pregnant females followed by appropriate management is essential.